Cervical cystic lymphangioma in a child - Ulrich Opoko; Rachid Aloua; Iro Salissou; Ouassime Kerdoud; Zahra Hmoura; Faiçal Slimani (Elsevier, 2021)
Cystic lymphangiomas are rare benign dysembryoplasias of the lympho-ganglionic system, responsible for a tumor syndrome by angiolymphatic proliferation. They can occur everywhere in the body, but cervicofacial localizations are the most common. They represent between 2.6 and 5% of benign congenital cervical masses, and their clinical revelation is generally very early, in the first two years of life.Several therapeutic means exist but only surgery is classically recommended.We report here a case of a large cystic lymphangioma in an 18-month-old child, treated by surgery and confirmed by histology.